Follicle-Stimulating Hormone Regulates igfbp Gene Expression Directly or via Downstream Effectors to Modulate Igf3 Effects on Zebrafish Spermatogenesis - Safian, Diego; van der Kant, Henk J. G.; Crespo, Diego; Bogerd, Jan; Schulz, Rüdiger W. (Frontiers in Endocrinology, 2017)
Previous work showed that pharmacological inactivation of Igf binding proteins (Igfbps), modulators of Igf activity, resulted in an excessive differentiation of type A undifferentiated (Aund) spermatogonia in zebrafish testis in tissue culture when Fsh was present in the incubation medium. Using this testis tissue culture system, we studied here the regulation of igfbp transcript levels by Fsh and two of its downstream effectors, Igf3 and 11-ketotestosterone (11-KT). We also explored how Fsh-modulated igfbp expression affected spermatogonial proliferation by adding or removing the Igfbp inhibitor NBI-31772 at different times. Fsh (100 ng/mL) decreased the transcript levels of igfbp1a, -3 and -6a after one or three days, while increasing igfbp2a and -5b expression, but only after five days of incubation. Igf3 down-regulated the same igfbp transcripts as Fsh but with a delay of at least four days. Interestingly, 11-KT increased the transcripts (igfbp2a and 5b) that were elevated by Fsh and decreased those of igfbp6a, as did Fsh, while 11-KT did not change igfbp1a or -3 transcript levels. To evaluate Igfbps effects on spermatogenesis, we quantified under different conditions the mitotic indices and relative section areas occupied by the different spermatogonial generations (type Aund, type A differentiating (Adiff), or type B (B) spermatogonia). Igf3 (100 ng/mL) increased the area occupied by Adiff and B while decreasing the one for Aund. Interestingly, a concentration of Igf3 that was inactive by itself (25 ng/mL) became active in the presence of the Igfbp inhibitor NBI-31772 and mimicked the effect of 100 ng/mL Igf3 on spermatogonia. Studies exploiting the different dynamics of igfbp expression in response to Fsh and adding or removing NBI-31772 at different times showed that the quick down-regulation of three igfbp as well as the delayed up-regulated of two igfbps all support Igf3 bioactivity, namely the stimulation of spermatogonial differentiation. We conclude that Fsh modulates, directly or via androgens and Igf3, igfbp gene expression, supporting Igf3 bioactivity either by decreasing igfbp1a, -3, -6a or by increasing igfbp2a and -5b gene expression.